An ecological approach to understanding university English teachers’ professional agency in implementing formative assessment - Jiang, Yuhong; Li, Jia; Wang, Qiang (Frontiers in Psychology, 2022)
As a sub-realm of Language Teacher Psychology (LTP), teachers’ professional agency has gained significant attention from educational practitioners and teachers. The aim is to better discern teachers’ professional development and teaching effectiveness with a view to ensuring the quality of language teaching. International literature concerning teachers’ professional agency has noted a shift from knowledge training to vocational development in relation to teachers’ experience in decision making. Yet, little research so far has scrutinized this specific issue in Chinese university settings, and the real picture of teacher agency needs further exploration. Besides, the multidimensional and complex nature of agency identifies the overwhelming research work in understanding its contents in detail based on the previous perspectives from individuals, society, and time. To this end, the ecological understanding of professional agency reframed the theoretical basis of this study, prone to explore how teachers’ experience could be examined in relation to individual capacity, resources, and structural and contextual variables. The study was conducted in Chinese university settings in response to the research gap related to understanding professional agency. Quantitative and qualitative data from questionnaires, interviews, and classroom observations with 116 university teachers in China demonstrated that the enactment of professional agency rested on the interplay between temporal contexts, teacher capacity, and beliefs, especially in the instructional community. The findings revealed that university teachers at different stages of career development manifested variability in exercising their professional agency in relation to adapting or adopting existing teaching concepts, methods, or approaches. Mounting evidence revealed some enablers and constraints in relation to formative assessment, time impact, classroom interaction, and school culture. Emphasizing the interaction between individuals’ ability and their engagement with the professional environment, the findings provide insights into theoretical implications associated with ecological theory and enhance the practical discussion about promoting professional development for novice, mid-career, and veteran English teachers at the university level.